Control of stain geometry by drop evaporation of surfactant containing dispersions - Erbil, H. Yildirim (Elsevier, 2015)
Control of stain geometry by drop evaporation of surfactant containing dispersions is an important topic of interest because it plays a crucial role in many applications such as forming templates on solid surfaces, in ink-jet printing, spraying of pesticides, micro/nano material fabrication, thin film coatings, biochemical assays, deposition of DNA/RNA micro-arrays, and manufacture of novel optical and electronic materials. This paper presents a review of the published articles on the diffusive drop evaporation of pure liquids (water), the surfactant stains obtained from evaporating drops that do not contain dispersed particles and deposits obtained from drops containing polymer colloids and carbon based particles such as carbon nanotubes, graphite and fullerenes. Experimental results of specific systems and modeling attempts are discussed. This review also has some special subtopics such as suppression of coffee-rings by surfactant addition and stick-slip behavior of evaporating nanosuspension drops. In general, the drop evaporation process of a surfactant/particle/substrate system is very complex since dissolved surfactants adsorb on both the insoluble organic/inorganic micro/nanoparticles in the drop, on the air/solution interface and on the substrate surface in different extends. Meanwhile, surfactant adsorbed particles interact with the substrate giving a specific contact angle, and free surfactants create a solutal Marangoni flow in the drop which controls the location of the particle deposition together with the rate of evaporation. In some cases, the presence of a surfactant monolayer at the air/solution interface alters the rate of evaporation. At present, the magnitude of each effect cannot be predicted adequately in advance and consequently they should be carefully studied for any system in order to control the shape and size of the final deposit. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Drop evaporation; Surfactant; Nano-suspension drops; Stain formation; Contact angle; Stick-slip movement